Extreme UV spectroscopy measurements and analysis for tungsten density studies in the WEST tokamak. (1st October 2022) - Guirlet, R; Desgranges, C; Schwob, J L; Mandelbaum, P; Boumendjel, M Y; ,
Abstract: The VUV emission of tungsten in WEST is measured by an absolutely calibrated grazing incidence spectrometer of the Schwob–Fraenkel type, which can scan the lower half of the plasma. We have analysed the detected spectral lines in the range 120–140 Å and compared their behaviour with calculations and published information. We obtained an unambiguous identification of four intense and well-resolved spectral lines emitted by W 42+ -W 45+ close to the magnetic axis in the analysed experiments. The measured spectral-line brightnesses are used to assess the Tungsten density in the emission region. In the case of a scanning line of sight, we investigate the possibility to calculate the Tungsten density profile from the angular brightness profiles. In a case of a fixed line of sight, we deduce from the measurements the core Tungsten density profile evolution during a radiative collapse.